Melia dubia: a potential tree and source of income generation under agroforestry - Sirohi, Chhavi; Bangarwa, K S; Dhillon, R S (Indian Farming, 2018)
Each tree of appropriate girth can fetch up to Rupees 4,000 to 5,000 per tree over a 6 to 7 year period, if sold as veneer. It plays a vital role in multifarming of sheep, goat and dairy farming. In this way due to its various uses, it can become a most important income generating tool among farmers.